The effects of differential rearing and abstinence period on post-synaptic glutamate receptors and amphetamine seeking - Garcia, Erik Joseph (Kansas State University, 2017)
Drug addiction is a chronic cyclical disease characterized by periods of drug use and abstinence. Drug craving increases as a function of abstinence period, such that longer periods of abstinence result in greater feelings of craving. Longer periods of abstinence may render cues to become more powerful motivators of drug seeking behavior because of the greater craving response. Neurobiological evidence suggests that changes in glutamatergic transmission in the nucleus accumbens (NAc) plays a pivotal role in the incubation of craving and drug seeking motivation. Specifically, the upregulation of Ca²⁺ permeable AMPA receptors may increase drug seeking following the presentation of a drug cue. Environmental housing manipulations also change the expression of metabotropic glutamate receptors (mGlur) and psychostimulant self-administration. In the current experiments, Sprague-Dawley rats were reared in enriched (EC) or isolated (IC) conditions from PND 21-51. Then rats were implanted with indwelling jugular catheters and allowed to self-administer amphetamine (0.1 mg/kg/infusion) or saline paired with a cue light for 16 days for 1h. Then rats went through a forced abstinence period of 1 day and were then tested in a cue-induced seeking test. Immediately after the seeking test, half the rats were sacrificed and the NAc was dissected and prepared for western blot analyses. The other half of rats rested for 40 days and were tested again in the cue-induced seeking test. Immediately following the seeking test, rats were sacrificed and their NAc was dissected. Factorial ANOVA results indicate that rearing in the IC environment increased drug seeking when compared to EC rats after 1 day of abstinence and after 40 days of abstinence, but drug seeking did not increase after 40 days. Rats in the saline groups showed an increase in seeking after 40 days of abstinence, providing evidence of increased responding. Saline responding was significantly lower when compared to rats that responded for amphetamine. When rats self-administered saline, generally IC rats had more responding than EC rats. Western blot analyses indicated that expression of AMPA subunits GluA1, and GluA2, as well as metabotropic glutamate receptors 1 and 5 (mGlur1, and mGlur5) were not different across the experimental groups, suggesting another mechanism could be implicated in drug seeking after short and long abstinence periods. These results suggest that early life experience can have long lasting effects into adulthood and increase the vulnerability of drug abuse. Our results provide mixed results of incubated seeking. Positive early life experiences reduce drug seeking motivation after short and long abstinence periods, providing evidence for further research to examine how early life experience changes the reward seeking and subsequent structures in the mesocorticolimbic pathway.
Keywords: enrichment; differential rearing; drug seeking; glutamate receptor; incubation; nucleus accumbens